KUALITAS PELAYANAN PEMERINTAHAN DESA DALAM IMPLEMENTASI UNDANG-UNDANG NO. 6 TAHUN 2014 DI DESA NAGARAWANGI KECAMATAN RANCAKALONG KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Dedi Kusmana (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
The Village Governance is a government organization which has function for serving the public’s needs. A good service quality is the expectation of the public as the consumers, by providing and improving the services to the community and also providing an equal and fair services. Giving the service is a major duty of apparatus, both village apparatus and agencies. This research aims to describe the quality of government services in the Nagarawangi village, Rancakalong District, and inhibiting factors of service quality of village governance. Various services provided by the village governance are common public services and administrative services. Researcher focused more on administrative services, it is taken because researcher felt there were issues of administrative services that need more attention. One of them is there were a lack of clarity of the information service procedure and the service simplementation in the Rancakalong District, Nagarawangi village. The focus of this research is the quality of village governance services and supporting factors of service quality in the District Rancakalong Nagarawangi village. The type of this research is descriptive research with a qualitative approach. Informants in the research were Village Apparatus, BPD and the societies of Nagarawangi Village, Rancakalong District as the recipients of services. Data collection techniques which is used by the researcher were observation, interviews and documentation. Data analysis was performed with data reduction, data presentation and then drawing the conclusions. Results of this research, based on the findings based on an analysis of fivedimensional field of service quality indicators, showed that the public services is going according to the job description. The five dimensions are Tangible, realibility, responsivenes, assurance and empathy. It was evident from the data obtained from the analysis of the five dimensions of service quality, overall already run well. But there are still some things that have not been optimal. Keywords: quality of service